2019
DOI: 10.1108/ijph-11-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and wellbeing benefits from a prisons horticultural programme

Abstract: Purpose In the context of current prison safety and reform, the purpose of this paper is to discuss findings of an impact evaluation of a horticultural programme delivered in 12 prisons in North West England. Design/methodology/approach The programme was evaluated using quantitative and qualitative methods, including Green Gym© questionnaires, the Warwick Edinburgh Mental Wellbeing Scale (WEMWBS) and Biographic-Narrative Interpretive Method interviews. Findings Against a backdrop of high rates of suicide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Research has suggested that self-reported change in antisocial attitudes may not provide valid information about change in risk of recidivism as a result of intervention (Howard and van Doorn, 2018) and therefore other methods may be more beneficial in predicting whether interventions will truly 'rehabilitate' their participants. Similar studies have discovered that while quantitative measures may not reveal a significant difference in change scores, qualitative interviews reveal benefits of the intervention which would otherwise not be seen (Farrier et al, 2019). This emphasizes the need for mixed methods in this research area which has been suggested in previous literature (Blagden et al, 2016).…”
Section: Risk and Protective Factorsmentioning
confidence: 72%
See 3 more Smart Citations
“…Research has suggested that self-reported change in antisocial attitudes may not provide valid information about change in risk of recidivism as a result of intervention (Howard and van Doorn, 2018) and therefore other methods may be more beneficial in predicting whether interventions will truly 'rehabilitate' their participants. Similar studies have discovered that while quantitative measures may not reveal a significant difference in change scores, qualitative interviews reveal benefits of the intervention which would otherwise not be seen (Farrier et al, 2019). This emphasizes the need for mixed methods in this research area which has been suggested in previous literature (Blagden et al, 2016).…”
Section: Risk and Protective Factorsmentioning
confidence: 72%
“…The specific population of young adult male offenders may also play a role in the effectiveness of the quantitative measure as their social context may explain socially desirable responding to such measures (Howard and van Doorn, 2018), and may influence the truthfulness or accuracy of their answers. Existing studies have encountered similar issues here with response bias, where participants ticked all answers or left questionnaires incomplete (Farrier et al, 2019).…”
Section: Risk and Protective Factorsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the context of the current UK prison reform agenda that seeks effective and sustainable prisoner management and rehabilitation (Ismail & de Viggiani, 2018) and against a backdrop of public sector constraint and concern about the high incidence of violence, suicide, self-harm and poor mental health among prisoners, GOOP has empirically demonstrated that gardening can benefit the physical and mental health and wellbeing of prisoners and make a significant contribution to the creation of safe, secure, supportive and health-enhancing environments (Baybutt et al, 2018;Farrier, Baybutt and Dooris, 2019;Farrier and Kedwards, 2015). These impacts are increasingly widely recognised as being the result of joined-up 'whole system' working.…”
Section: Growing Food In Prisons In England and Walesmentioning
confidence: 99%